Approach to patients with cleft lip and palate in orthodontics - Yasin Akbulut (Wolters Kluwer Medknow Publications, 2020)
Cleft lip and palate (CLP) are the most commonly observed congenital anomaly in the craniofacial region, which are observed in one in every one thousand children and caused by multifactorial factors. CLP occur due to the inability of embryonic protrusions, which forms the roof of the mouth with the maxillary bone, to integrate completely. Due to the scar tissue formed as a result of the operation conducted for dental problems, such as missing teeth or extra teeth, location anomalies, enamel defects, and anomalies of size, formation, and eruption, CLP can cause developmental problems, problems in speech due to difficulties in phonation, and hearing problems due to frequently experienced otitis media. CLP treatment requires a multidisciplinary approach. For the CLP treatment to succeed, it is very important for a team that consists of an orthodontic specialist, ENT specialist, audiologist, psychologist, dentist, and speech therapist to work in harmony. The treatment process of CLP starts as soon as the infant is born. The period of the first 6 months is the preoperative period. In this period, a feeding plaque implementation is conducted by an orthodontic specialist. Operations for lips are usually conducted between the 3rd and 6th months, whereas operations for palates are usually conducted between the 12th and 18th months. In mixed dentition, maxillary expansion and protraction, tooth location correction, and bone grafting are conducted. In continuous dentition, if constant orthodontic treatment is necessary, orthognathic surgical operations and prosthetic dentistry treatments are conducted. In CLP anomalies, the main aim is to educate future mothers and fathers about the factors that can be eliminated. For infants who are born with CLP, the treatment should be initiated without losing any time. The fact that the treatment of these patients is conducted at an esthetically and functionally satisfactory level will also improve the quality of life for both the patients and their families. Furthermore, in patients with CLP, esthetics, phonation, and speech, briefly, the external appearance should be emphasized with recurring operations and follow-ups and their mental states should not be ignored in addition to supporting them with psychological rehabilitation and a constant boost of morale.